2013
DOI: 10.2147/jmdh.s39133
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypoglycemia on daily life of type 2 diabetes patients in Ukraine

Abstract: This study evaluates the impact of hypoglycemia on the lives of Ukrainian patients with type 2 diabetes mellitus. The secondary objective was to explore patient–physician relationships and the attitudes of patients towards various informational resources on diabetes management. Three focus groups with 26 patients were conducted. Qualitative information was evaluated using content analysis. The results show that patients with type 2 diabetes mellitus in Ukraine are adapting to potential attacks of hypoglycemia;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
(61 reference statements)
0
7
0
1
Order By: Relevance
“…On the other hand, other studies have reported that patients with DM were aware of diabetes symptoms and complications, severity of their events and the actions required to manage them. In those studies, patients were not only able to adjust their lifestyle based on their metabolic needs but they also adapted their daily activities, work schedules and personal relationships to help prevent hypoglycaemic events [3234]. Different factors should be taken into consideration when dealing with patients with DM who are at higher risk of developing diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other studies have reported that patients with DM were aware of diabetes symptoms and complications, severity of their events and the actions required to manage them. In those studies, patients were not only able to adjust their lifestyle based on their metabolic needs but they also adapted their daily activities, work schedules and personal relationships to help prevent hypoglycaemic events [3234]. Different factors should be taken into consideration when dealing with patients with DM who are at higher risk of developing diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, problem-solving interventions should extend to include home-based programmes using telephone and telehealth applications in order to overcome barriers to participation such as difficulties in transportation [62]. Involving family, friends and the work environment could also have a positive impact on the patients’ diabetes management and well-being [34].…”
Section: Discussionmentioning
confidence: 99%
“…While the initial symptoms of hypoglycaemia warn patients of an hypoglycaemic event occurring, the symptoms can vary considerably between individuals [8]. The symptoms of hypoglycaemia can be categorised as autonomic symptoms (sweating, palpitations, shaking, hunger), neuroglycopenic symptoms (confusion, drowsiness, odd behaviour, speech difficulty, incoordination) and unspecific symptoms (headache, nausea) [8,9]. In severe cases, hypoglycaemia can lead to seizure, coma and death [6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of hypoglycaemia can be categorised as autonomic symptoms (sweating, palpitations, shaking, hunger), neuroglycopenic symptoms (confusion, drowsiness, odd behaviour, speech difficulty, incoordination) and unspecific symptoms (headache, nausea) [8,9]. In severe cases, hypoglycaemia can lead to seizure, coma and death [6,[8][9][10]. Hypoglycaemic episodes are typically characterized as either non-severe or severe, according to whether the person with diabetes can manage the event alone, or whether the hypoglycaemia event is associated with severe cognitive impairment requiring external assistance for recovery [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…При падении уровня сахара крови ниже 2,8 ммоль/л происходит нарушение сознания [4]. Пролонгация состояния гипогликемии приводит к расстройствам древних корковых образований ЦНС и диэнцефаль-ных структур, развитию грубых неврологических нару-шений с возможной гибелью больного [1].…”
unclassified